2016
DOI: 10.1021/acs.chemmater.6b01499
|View full text |Cite
|
Sign up to set email alerts
|

Cu2ZnSnS4 Thin Films Generated from a Single Solution Based Precursor: The Effect of Na and Sb Doping

Abstract: A new solution based route for depositing Cu 2 ZnSnS 4 (CZTS) thin films is described, focusing on the effects of Sb and Na co-doping. X-ray diffraction and Raman spectroscopy confirm formation of the kesterite phase with a measurable improvement in crystallinity upon doping. A sharp band gap absorption edge at 1.4 eV is determined from diffuse reflectance measurements, whilst improvement in the photoluminescence yield and sharpening of the band-to-band emission spectra are observed in the presence of Na and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
69
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 29 publications
3
69
1
Order By: Relevance
“…Sb doping showed an overall improvement in key CZTS device metrics such as V OC and fill factor, which comes as a result of a complex interplay of remediation of elemental disorder and improvement of band alignment. Figure 13(b) illustrates the decrease of the isotropic thermal parameter in Sn and Cu sites (as obtained by XRD structure refinement) upon Sb and Na doping, respectively, suggesting a significant decrease in disorder at these sites [129]. The effect of Sb on Sn disorder can be simply rationalized by their similar ionic radii (Sb, Z=51 to Sn, Z=50).…”
Section: Germanium (Ge)mentioning
confidence: 95%
See 3 more Smart Citations
“…Sb doping showed an overall improvement in key CZTS device metrics such as V OC and fill factor, which comes as a result of a complex interplay of remediation of elemental disorder and improvement of band alignment. Figure 13(b) illustrates the decrease of the isotropic thermal parameter in Sn and Cu sites (as obtained by XRD structure refinement) upon Sb and Na doping, respectively, suggesting a significant decrease in disorder at these sites [129]. The effect of Sb on Sn disorder can be simply rationalized by their similar ionic radii (Sb, Z=51 to Sn, Z=50).…”
Section: Germanium (Ge)mentioning
confidence: 95%
“…Group V 6.1. Antimony (Sb) In a large study assessing over 200 solar cells, Tiwari et al concluded that Sb and Na co-doping substantially improve the efficiency of Cu 2 ZnSnS 4 (CZTS) prepared by thermolysis of molecular precursors as exemplified in figure 13(a) [129]. The introduction of Sb as a dopant was inspired by the positive effects on grain growth previously demonstrated in CIGS [130].…”
Section: Germanium (Ge)mentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6] The CZTSSe solar cells on classical rigid soda glass (SLG) substrates have made good progress, with the highest PCE of 12.6% for the CZTSSe solar cells demonstrated by IBM. 7 However, the efficiency of the CZTSSe solar cells on exible substrates (with a PCE of 6.9%) is still lower than those on SLG substrates.…”
Section: Introductionmentioning
confidence: 99%